Liberalization with Endogenous Institutions: A Comparative Analysis of Agricultural Reform in Africa, Asia, and Europe - Johan F. M. Swinnen; Anneleen Vandeplas; Miet Maertens (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2009)
Thirty years ago, a vast share of the poor and middle income countries were heavily state-controlled. The effects of the liberalizations in the 1980s and 1990s differed strongly between regions in Africa, Asia and Europe. This paper first documents these differences in refirm effects in a comparative framework and then develops a model to firmally analyze how liberalization affects production and income distribution when institutions that govern production and exchange are also affected. We derive hypotheses on how the endogenous institutional adjustments affect the supply response to the liberalizations. We use these insights to forward a series of explanations on the differences in perfirmance across countries following liberalization.
Keywords: O12; O18; O43; O57; Q12; Q13; 330; Agricultural supply chains; growth; development; regional comparisons